Explorations in the History and Heritage of Machines and Mechanisms : Proceedings of the 2018 HMM IFToMM Symposium on History of Machines and Mechanisms /: Proceedings of the 2018 HMM IFToMM Symposium on History of Machines and Mechanisms. ([2019]) - Unknown
No abstract available